LEGAL ANALYSIS OF BROADCASTING ETHICS ON FTV SUARA HATI WIFE IN INDOSIAR - Annisa, Annisa; Uyun, Zafirah Quroatun (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The main problem in this thesis is the wedding procession that is not shown in the FTV Suara Hati Istri episode